Soil microbes support Janzen’s mountain passes hypothesis: The role of local-scale climate variability along a tropical montane gradient - Feng, Yifan; Wang, Jianbin; Zhang, Jian; Qi, Xuming; Long, Wenxing; Ding, Yi; Liu, Lan (Frontiers in Microbiology, 2023)
Tropical montane ecosystems are the centers of biodiversity for many macroorganisms and microorganisms. Daniel Janzen (1967) proposed that mountain climate variability plays a critical role in sustaining extremely high biodiversity in tropical mountains. We test this hypothesis for soil bacteria and fungi along a 265-1,400 m elevational gradient on Hainan Island of tropical China, representing diverse vegetation types from deciduous monsoon forest to cloud forest. We found that bacterial and fungal diversity declined as elevation increased, and the compositional dissimilarity of both groups increased with increased separation in elevation, although changes in bacteria were larger than in fungi. Seasonal alterations and range of soil moisture in the growing season were found to be the dominant drivers of fungal richness and Shannon diversity, whereas soil pH was the major regulator of bacterial diversity. Compositional dissimilarities in bacteria and fungi were best predicted by climate, particularly seasonal changes in soil temperature, with weaker influences of soil physicochemistry and vegetation. The dominant effect of seasonality in soil temperature was further detected in cloud forests, which harbored a higher proportion of unique bacterial species and compositional dissimilarity of bacterial and fungal communities. Our findings suggest that local-climate variability plays a crucial role in structuring the distribution of soil microbial communities along the tropical montane gradient, which in general supports the predictions of Janzen's mountain passes hypothesis and indicates that soil microbes in tropical montane ecosystems are particularly vulnerable under changing climate.